WOMEN’S LEADERSHIP IN ISLAM: AN ANALYSIS OF JURGEN HABERMAS’S PHILOSOPHY - Fatrawati Kumari (CV. Lafadz Jaya, 2026)
Indeed, women possess the same ability to lead as men. However, culture and religion, including Islam, often seem to provide little space for women to develop their leadership potential. Various arguments have been put forward, cultural, social, and religious, to restrict women’s leadership. Nevertheless, historical facts demonstrate that women have proven capable of becoming competent leaders since the classical Islamic period up to the present day. Quantitatively, the number of Muslim women who hold leadership positions, whether in the executive, legislative, or judicial branches, has become countless. This reality serves as a reversal of the negative stigma against women, which Habermas refers to as an ideology critique. Moreover, Islam itself teaches the values of equality and respect toward women, just as it does toward men. Therefore, a study examining the issue of Muslim women’s leadership through the lens of Habermas’s philosophy is necessary. This research is descriptive-qualitative in nature, with the material object being women’s leadership in Islam and the formal object being Habermas’s philosophy. The study produced two main findings: First, Muslim women have the right to become leaders according to Islamic teachings and the views of Islamic scholars. Second, the reality of women in leadership illustrates that their struggle to claim the right to lead, just as men do, can be understood through Habermas’s concept of ideology critique, namely a critique against the rigid interpretation of Qur’anic verses and hadith. This critique employs cultural, historical, and linguistic approaches, as both the Qur’an and hadith, being the foundational sources of Islamic life, including leadership, carry socio-cultural and historical contexts. Thus, their essential meanings can be understood more fully.